STUDIES ON WOUND HEALING ACTIVITY OF SOME EUPHORBIA SPECIES ON EXPERIMENTAL RATS - Ahmed, Sarfaraz; Yousaf, Muhammad; Mothan, Ramzi A.; Al-Rehaily, Adnan J. (African Journal of Traditional, Complementary and Alternative Medicines, 2016)
Background: Plants of Euphorbiaceae are used in folkloric medicines in variety of ailments and well known for chemical diversity of their isoprenoid constituents. This study was carried out to explore the preliminary wound healing potential of four Euphorbia species (E. consorbina 1, E. consorbina 2, E. inarticulata, E. balsamifera and E. schimperi). Materials and Methods: Excision wound surface of the animals were topically treated with ethyl acetate and methanol extracts of plants at a dose of 400 mg/kg body weight for twenty days. Povidone-iodine ointment was used as a reference drug. Wound contraction measurement and period of epithelialization were used to assess the effect of plants extracts on wound repairing. Results: The groups treated with methanol extracts of E. balsamifera and E. schimperi showed profound effects, high rate of wound contraction (100%) and decrease in epithelization period 19.00±0.40 and 18.50±0.64 respectively, followed by methanol extracts of E. consorbina 2, ethyl acetate extract of E. inarticulata and ethyl acetate extracts of E. consorbina 2 which showed significant (P <0.001) wound contraction and decrease in epithelization period. Conversely ethyl acetate extract of E. consorbina 1, E. balsamifera and E. schimperi and methanol extract of E. Consorbina 1 and E. Inarticulata treated groups was not showing significant wound healing. Methanol extracts of E. balsamifera and E. schimperi were also tested for their safety margin and found safe up to dose of 2000mg/kg body weight. Conclusion: Topical application of methanol extracts of E. balsamifera and E. schimperi have potential wound healing activity which is identical with standard drug Povidone-iodine.